The Contribution of the School Musical Groups to the Society - Bermell Corral, Mª Ángeles; Alonso Brull, Vicente (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2014)
We know that from a scientific perspective, activating certain musical stimuli produces brain activation. With the school, musical ensembles required previously activated the techniques of hearing and interpretation of individually to achieve the group, motor, perceptual, cognitive skills and affective processes enable and socialization. In this way, the attention to diversity would not be excluded. Music, in short, favors the development of the person in all its dimensions, which results in an improvement of the quality of life and a breakthrough to personal, family, school, clinical and social level. The musical activity is as an introduction into the irreplaceable cultural framework system. RESUMEN